2003
DOI: 10.1094/mpmi.2003.16.12.1094
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Mediated Transcriptional Changes in Arabidopsis thaliana

Abstract: Nitric oxide (NO) is an essential regulatory molecule in several developmental processes and in the stress response in both animal and plant systems. Furthermore, key features of plant resistance to pathogens have been shown to depend on NO production, e.g., defense gene expression and the activation of a hypersensitive reaction (HR) in synergy with reactive oxygen species (ROS). Due to the many possible mechanisms of NO action, a clear picture of its involvement in plant resistance to pathogens is far from be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(108 citation statements)
references
References 73 publications
2
102
0
4
Order By: Relevance
“…It has been shown that NO regulates a number of physiological processes directly by affecting gene transcription (Huang et al, 2002;Wang et al, 2002;Polverari et al, 2003;Parani et al, 2004;Shoulars et al, 2008). NO can also regulate specific physiological and developmental processes through its interplay with other small biomolecules.…”
mentioning
confidence: 99%
“…It has been shown that NO regulates a number of physiological processes directly by affecting gene transcription (Huang et al, 2002;Wang et al, 2002;Polverari et al, 2003;Parani et al, 2004;Shoulars et al, 2008). NO can also regulate specific physiological and developmental processes through its interplay with other small biomolecules.…”
mentioning
confidence: 99%
“…Not surprisingly, several proteomic studies have recently reported that H 2 O 2 , NO-donors, and biotic and abiotic stresses applied to plants may affect the redox state of reactive protein cysteines, in addition to affecting their transcriptomic and proteomic profiles Polverari et al, 2003;Parani et al, 2004;Lindermayr et al, 2005;Herbette et al, 2006;Roth et al, 2006;Sarry et al, 2006;Besson-Bard et al, 2008;Romero-Puertas et al, 2008;Astier et al, 2011). Because of the high reactivity of its catalytic Cys, cytosolic glyceraldehyde 3-P dehydrogenase (GAPDH) has been identified as a target of different types of redox modifications (Hancock et al, 2005(Hancock et al, , 2006Lindermayr et al, 2005;Holtgrefe et al, 2008;Bedhomme et al, 2012).…”
mentioning
confidence: 99%
“…[5][6][7][8] It has been demonstrated that NO cooperates with H 2 O 2 to activate the hypersensitive reaction in plants. [9][10][11][12] However, the interaction of NO and H 2 O 2 is still far from being clearly elucidated. [13][14][15][16][17] We have recently demonstrated that NO and H 2 O 2 can act as an upstream signaling molecule to modulate the dynamic microtubule cytoskeleton during the defense responses to Verticillium dahliae (VD) toxins in Arabidopsis.…”
mentioning
confidence: 99%